ER, PR, HER2/NEU STATUS AND RELATION TO CLINICOPATHOLOGICAL FACTORS IN BREAST CARCINOMA - Yadav, Ritu; Sen, Rajeev; Chauhan, Preeti (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The role of hormone receptors as a prognostic and therapeutic tool in breast cancer is widely accepted. The aim of this study was to the analysis of steroid receptor status in breast cancer with clinic pathological characteristics. Methods: In the present study, immunohistochemical assay of two hundred tumor block of patients of breast carcinoma was performed to know the hormone receptor status as well as histological examination. Results: 150 samples were grouped to study hormonal status and their relation with clinic-pathological factors. The results in the present study documented the 42.3 %, 37.6 % and 56.2 % expression rate of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor-2 (Her2/neu) (. The negative expression of ER, PR receptors found higher (57.7 %, 62.4 % respectively). However, Her2/neu positive expression found higher than negative expression (43.8 %). An inverse correlation of Her2/neu expression with ER and PR expression was observed (p=0.007). A significant association of tumor size was observed with ER and PR expression (p=0.02 & p=0.04 respectively). However, no statistically significant association was observed between Her2/neu expression and tumor size (p=0.84).<4 positive lymph nodes showed more no reactivity of the receptors (ER, PR & Her2/neu) than>4 positive lymph nodes. No significant association of lymph node status and histological types was found with receptor expression. Conclusion: In conclusion further functional analyzes of ER, PR and Her2 receptors are needed to investigate the effects of compounds in inhibiting cancer in humans. Keywords: Breast carcinoma, Estrogen, Her-2/neu receptor, Immunohistochemistry, Progesterone Â